Platform design for lifelog-based smart lighting control. (November 2020) - Cho, Younjoo; Seo, Jiyoung; Lee, Heesu; Choi, Seri; Choi, Anseop; Sung, Minki; Hur, Yoonseok
Abstract: Lifelog refers to daily life records of individuals and includes their environmental, activity, emotional, and biometric information. The utilization of lifelogs makes it possible to provide a personalized lighting environment in line with a user's characteristics. However, no such customized lighting environment has been proposed thus far because methods for collecting and classifying the necessary data and a platform for synthesizing the data are not available. Therefore, in this study, the concept of the lifelog-based smart lighting control is introduced, and lifelog collection methods and a method to recommend the appropriate lighting environment for an individual by analyzing the collected information are proposed. Sensors, lighting controllers, and control interfaces required for lifelog-based smart lighting control were installed in a mock-up space, a machine learning server was set up, and a platform for implementing the optimal lighting environment was constructed by connecting these devices to the cloud. The platform constructed in this study creates a personalized lighting environment by utilizing lifelogs that are divided into emotional information collected via instant message (IM) text analysis, activity information collected using a location and activity tracker, and environmental information collected from weather data. Highlights: A platform for lifelog-based smart lighting control was constructed. Methods for collecting and analyzing the emotional, activity, and environmental information were presented. Based on emotion analysis through instant messages, lighting can be controlled by the user's emotion. Lighting environment that relieves fatigue can be provided by the fatigue index calculated using activity data. Using weather data, the emotional changes according to the weather can be performed through lighting control.